Germination and seedling establishment in cashew (Anacardium occidentale L.): An interaction between seed size, relative growth rate and seedling biomass - M.G. Nayak and G.S. Mohana, Babli Mog, J.D. Adiga (Journal of Plantation Crops, 2017)
Seeds of cashew were used to determine the effect of seed mass (5.2 to 7.8 g) on germination, seedling emergence and growth under nursery conditions. Germination percentage and germination time showed significant correlation with seed mass. Large sized seeds had higher germination percentage (81.6%) and produced more vigorous seedlings. Per cent seedling emergence was related to seed mass with large sized seeds exhibited faster emergence. Seed mass significantly affected seedling survival and survival rate was high in seedlings arising from large sized seeds (62.9%). Seedling vigor expressed in terms of shoot and root length, leaf number, leaf area and total dry matter was significantly affected by seed mass. Seedlings that emerged from large sized seeds showed better growth and produced heavier seedlings as compared to medium sized seeds. RGR showed significant variation (0.152 to 0.240 g g-1day-1) among two seed size classes positively correlated with seed mass, leaf area (LA), unit leaf rate per unit leaf area (ULRM), root to shoot ratio (R/S) and root mass ratio (RMR) and negatively with stem mass ratio (SMR). The study concluded that the seed mass and RGR have influence on seedling growth and success of seedling establishment in cashew.